Comparison of T2 Quantification Strategies in the Abdominal-Pelvic Region for Clinical Use. Issue 6 (10th June 2022) - Draveny, Robin; Ambarki, Khalid; Han, Fei; Hilbert, Tom; Laurent, Valérie; Morel, Olivier; Bertholdt, Charline; Beaumont, Marine
Abstract : Objectives: The aim of the study was to compare different magnetic resonance imaging (MRI) acquisition strategies appropriate for T2 quantification in the abdominal-pelvic area. The different techniques targeted in the study were chosen according to 2 main considerations: performing T2 measurement in an acceptable time for clinical use and preventing/correcting respiratory motion. Materials and Methods: Acquisitions were performed at 3 T. To select sequences for in vivo measurements, a phantom experiment was conducted, for which the T2 values obtained with the different techniques of interest were compared with the criterion standard (single-echo SE sequence, multiple acquisitions with varying echo time). Repeatability and temporal reproducibility studies for the different techniques were also conducted on the phantom. Finally, an in vivo study was conducted on 12 volunteers to compare the techniques that offer acceptable acquisition time for clinical use and either address or correct respiratory motion. Results: For the phantom study, the DESS and T2-preparation techniques presented the lowest precision ( ρ 2 = 0.9504 and ρ 2 = 0.9849 respectively), and showed a poor repeatability/reproducibility compared with the other techniques. The strategy relying on SE-EPI showed the best precision and accuracy ( ρ 2 = 0.9994 and Cb = 0.9995). GRAPPATINI exhibited a very good precision ( ρ 2 = 0.9984). For the technique relying on radial TSE, the precision was not as good as GRAPPATINI ( ρ 2 = 0.9872). The in vivo study demonstrated good respiratory motion management for all of the selected techniques. It also showed that T2 estimate ranges were different from one method to another. For GRAPPATINI and radial TSE techniques, there were significant differences between all the different types of organs of interest. Conclusions: To perform T2 measurement in the abdominal-pelvic region, one should favor a technique with acceptable acquisition time for clinical use, with proper respiratory motion management, with good repeatability, reproducibility, and precision. In this study, the techniques relying respectively on SE-EPI, radial TSE, and GRAPPATINI appeared as good candidates.